Catheter malposition analysis of totally implantable venous access port in breast cancer patients - Liu, Wenbo; Han, Qingzheng; Li, Lin; Chi, Jiangrui; Liu, Xinwei; Gu, Yuanting (Frontiers in Surgery, 2023)
Background To investigate the occurrence of catheter malposition in breast cancer patients undergoing Totally Implantable Venous Access Port (TIVAP) implantation and analyze the effect of TIVAP implantation site on the incidence of catheter malposition. Methods Clinical data of Breast cancer patients underwent TIVAP implantation in our department from 2017 to 2021 was collected by reviewing the electronic medical records. The catheter malposition rate, location and management of malposed catheters in TIVAP implantation were analyzed. We divided the patients into the left internal jugular vein (IJV) group and the right IJV group according to the site of TIVAP implantation and compared the difference in the catheter malposition incidence between the two groups. In addition, we counted the catheter malposition rate of TIVAP implantion via the left and right IJV in right breast cancer patients to analyze the effect of tumor status on the side of TIVAP implantation on the catheter malposition rate. Results A total of 1,510 catheters were implanted in 1,504 patients, and 16 (1.06%) had catheter malposition. The catheter malposition rate was 4.96% (7/141) for TIVAP implanted via the left IJV and 0.66% (9/1,369) for right IJV, with a statistically significant difference (χ2 = 18.699, P < 0.05). 743 TIVAPs were implanted in patients with right-sided breast tumor, of which the incidence of catheter malposition was 5.15% (7/136) for TIVAP implanted via left IJV and 0.82% (5/607) for right IJV, with a statistically significant difference (χ2 = 10.290, P < 0.05). Malposed catheters were found in the subclavian vein, IJV, brachiocephalic vein, internal thoracic vein, undefined collateral veins, and outside the blood vessels. All malposed catheters were successfully adjusted to the proper position by simple manipulative repositioning or percutaneous positioning with the assistance of digital subtraction angiography (DSA), except for 1 case was removed the port because the catheter tip was located outside the vessel. Conclusion The catheter malposition rate of ultrasound-guided TIVAP implantation via IJV is low, and the malposed catheter can be successfully adjusted to the proper position by simple manipulative repositioning or DSA-assisted percutaneous positioning, however, the catheter malposition incidence of TIVAP implanted via left IJV is higher than that via the right side.